CONTRIBUTING FACTORS TO EFL STUDENT DISENGAGEMENT - Dea Febriana; Asep Suparman (Institut Pendidikan Indonesia Garut, 2020)
Student disengagement is certainly one of big issues in education. It is believed to be the factor linked to some serious problems such as low achievement, disruptive behaviors, and dropouts. The objective of this study was to discover the sources of student disengagement. This study was carried out by conducting in-depths interviews with 18 students who were identified to be disengaged in the university. The interviews took place for around two weeks in one of private universities in Garut. From the findings, it was shown that student personality and teacher-associated factors are the most influential factors among all. Moreover, student disengagement may be caused by other factors such as academic shaming culture, heavy workloads, inappropriate textbook selection, inadequate facilities, unfavorable environment, and class scheduling